Agosto : una reunión familiar dificil de olvidar - Wells, John; Streep, Meryl, 1949-; Roberts, Julia; Speak Up (DVD (Speak Up), 2013)
A look at the lives of the strong-willed women of the Weston family, whose paths have diverged until a family crisis brings them back to the Oklahoma house they grew up in, and to the dysfunctional woman who raised them.